Հայկական ռէփ - Տօնոյեան, Մուշեղ (տպ. Atlas)
The paper is a path-breaking study on Armenian rap. It narrates the birth and the development of Armenian rap, from its inception in the early 2000s. The study focuses on the different Armenian groups that emerged in Armenia as well as the different albums they produced and dwells on their texts, their content and the messages they carry. The study examines the shifts in the wording, expressions, and language used in the texts within the two decades of the existence of Armenian rap, how it was accepted by the public and the reaction of the young generation. The paper affirms the existence of Armenian rap and raises some questions on its prospects and the directions it may take.
Keywords: Երգարուեստ